Appearance of Abnormal Cardiothoracic Ratio of Fetuses with Hemoglobin Bart’s Disease: Life Table Analysis - Wanapirak, Chanane; Sirichotiyakul, Supatra; Luewan, Suchaya; Srisupundit, Kasemsri; Tongprasert, Fuanglada; Tongsong, Theera (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Objective To determine the timeline of the first appearance of an increased CT ratio of fetuses with hemoglobin (Hb) Bart’s disease.Materials and Methods A prospective longitudinal study was conducted on pregnancies at risk for fetal Hb Bart’s disease. Sonographic markers including cardiothoracic (CT) ratio and middle cerebral artery peak systolic velocity (MCA-PSV) were serially assessed and recorded from the first trimester. The definite diagnosis of fetal Hb Bart’s disease based on DNA analysis (CVS), or fetal Hb typing (HPLC; cordocentesis) was performed at the first appearance of an increased CT ratio.Results Of 275 pregnancies at risk, 64 fetuses were finally proven to be affected and life table analysis was performed. Most affected fetuses showed an increased CT ratio in late first trimester and early second trimester, with median time of the first appearance at 13 weeks and all affected fetuses were detected at 23 weeks or less. The CT ratio yielded a sensitivity of 100 % at a gestational age of 23 weeks with a false-positive rate of 8 %. MCA-PSV appeared later than CT ratio. Only 9.4 % of affected cases developed abnormal MCA-PSV before an increased CT ratio.Conclusion The timeline of the first appearance of an increased CT ratio of fetuses with Hb Bart’s disease was established. This may help us identify Hb Bart’s disease among fetuses at risk in earlier gestation and proper schedules for serial ultrasound could be made more effectively.
Keywords: middle cerebral artery peak systolic velocity; first trimester; cardiothoracic ratio; life table analysis; hemoglobin Bart's disease